Numerical Modeling for Discrete Multibody Interaction and Multifeild Coupling Dynamics Using the SPH Method. (28th April 2015) - Halik, Azhar; Imin, Rahmatjan; Geni, Mamtimin; Jin, Afang; Mou, Yangyang
Abstract : Discrete multibody interaction and contact problems and the multiphase interactions such as the sand particles airflow interactions by Aeolian sand transport in the desert are modeled by using the different kernel smoothing lengths in SPH method. Each particle defines a particular kernel smoothing length such as larger smoothing length which is used to calculate continuous homogenous body. Some special smoothing lengths are used to approximate interaction between the discrete particles or objects in contact problems and in different field coupling problem. By introducing the Single Particle Model (SPM) and the Multiparticle Model (MPM), the velocity exchanging phenomena are discussed by using different elastic modules. Some characteristics of the SPM and MPM are evaluated. The results show that the new SPH method can effectively solve different discrete multibody correct contact and multiphase mutual interference problems. Finally, the new SPH numerical computation and simulation process are verified.